Study on adaptive-passive multiple tuned mass damper with variable mass for a large-span floor structure. (15th April 2020) - Wang, Liangkun; Shi, Weixing; Zhang, Quanwu; Zhou, Ying
Highlights: A novel APVM-MTMD system is proposed. APVM-MTMD can retune itself through varying its mass. A large-span floor structure is proposed as a case study. The frequency retuning function of APVM-MTMD is verified. APVM-MTMD can control human-induced vertical vibrations. Abstract: Floor structures, especially large-span floor structures, are sensitive to human-induced vibrations, which might cause a serviceability problem. Multiple tuned mass damper (MTMD) system is often used in the vertical vibration control of large-span floor structures. While it is difficult to determine the design parameters of each TMD in an MTMD system, a passive MTMD system still has the detuning shortcoming. In order to overcome this problem, an adaptive-passive variable mass multiple TMD (APVM-MTMD) system is proposed in this study. Each APVM-TMD in the system has a variable mass configuration and a microcontroller system consisting of an accelerometer, a control circuit board, and a driving device. Under ambient excitation, the control circuit board gathers the signals of the accelerometer on the floor, which can identify the dominant natural frequency of the primary structure where this APVM-TMD is located; this is done through the short time Fourier transformation (STFT)-based frequency identification algorithm. Then, each APVM-TMD can automatically control the driving device to retune itself by varying its mass. After retuning steps of all APVM-TMDs, the previous MTMD system becomes a new MTMD system with a different frequency distribution. A large-span floor structure is proposed as a case study. The original finite element model (FEM) is updated according to the in-situ test. In the updated model, an APVM-MTMD system is designed according to the previous model, then the frequency retuning function is verified. Finally, by applying several kinds of human-induced excitations, the vertical vibration control effect of the retuned MTMD system is compared with the mistuned one. The results show that the APVM-MTMD system can retune itself, and the retuned MTMD system has the best vibration control effect compared to the case without control and the mistuned MTMD system case.